Structural studies of integral membrane GPCR accessory proteins - Sladek, B (2013)
GPCR accessory proteins regulate the strength, efficiency and specificity of signal transfer upon receptor activation. Due to the inherent difficulties of studying membrane proteins in vitro and in vivo, little is known about the structure and topology of these small accessory proteins. Two examples of GPCR accessory proteins are the Melanocortin-2 receptor accessory protein (MRAP) and the Receptor-activity-modifying protein (RAMP) family. MRAP and RAMP1 are the main focus of this thesis in which they are thoroughly characterised by solution-state NMR and further biophysical techniques. The single-pass transmembrane domain protein MRAP regulates the class A GPCR melanocortin receptors. It is specifically required for trafficking the melanocortin-2-receptor from the endoplasmic reticulum to the cell surface and subsequent receptor activation. A remarkable characteristic of MRAP is its proposed native dual-topology, which leads to an antiparallel homodimeric conformation. Investigation of the biochemical and biophysical properties of MRAP revealed an α-helical transmembrane domain, and an α-helical N-terminal LD(Y/I)L-motif. Further efforts concentrated on establishing the homodimeric conformation of MRAP in vitro. RAMP1 facilitates receptor trafficking and alters the ligand specificity of the GPCR Class B receptors calcitonin receptors and calcitonin receptor-like receptors. Moreover, RAMP1 is required to act as a Calcitonin-gene-related peptide (CGRP) receptor (RAMP1). RAMP1 has been shown to form stable parallel homodimers in the absence of its cognate receptor. Its dimerisation and the possible dimerisation motif PxxxxP-motif were studied extensively. With the goal of understanding the mechanism of dimerisation and the role of GPCR accessory proteins I have used solution-state NMR in detergent micelles as my main technique. NMR provides unique possibilities for understanding the structure and dynamics of such small membrane proteins.